COMPARISON OF HYPOTENSIONARY POST-EXERCISE RESPONSE ON SEDENTARY YOUNG WOMEN (Fiep Bulletin - online, 2012)
The post-hypotension exercise is a phenomena that acts on the reduction on blood pressure when it is below the resting levels regarding hypotensive and normotensive individuals after their physical activity routine. Objective: This study aims at analyzing and comparing the acute effect of the aerobic and strength physical training performed by female youths regarding the hypertensive response after a physical activity routine. Methods: Ten female youths who did not use to perform any physical activity (age 16,1±1,1years old; body mass index 19,6±1,7kg/m²) performed two sessions: a non-stop 30-minute treadmill routine of effective training with an intensity ranging from 60% to 80% FCRES, with the Borg scale; the other session involved strength training which was performed by using eight kinds of exercise equipment regarding the upper and the lower limbs. The intensity was measured using the scale (OMNI-Res) after each set. The systolic, diastolic blood pressure and the mean arterial pressure was measured during the pre-exercise rest 10 minute as well as in the 15min, 30min and 45minute intervals. Data are expressed through the measurement of variability and standard deviation (±SD). Results: Regarding rest, there was some statistically significant intragroup reduction on the systolic blood pressure in the R30 and R45 intervals in both experimental sessions. Concerning the mean arterial pressure, some hypotension was noticed in the 30-minute interval regarding aerobic training and in the 45-minute set for both experiments. In the 30-minute set there was some intergroup difference. conclusion: In the sets that were analyzed, especially the 30(R30) and the 45 minute- intervals acute sessions of aerobic and strength training were very effective to reduce the systolic blood pressure and the mean arterial pressure of female youths who had a sedentary lifestyle, and the aerobic training was more effective to cause the post-exercise hypotensive effect.
Keywords: strength training; aerobic training; post-exercise hypotension.